Induction of skin ulcers in moon light gourami (Trichogaster microlepis) with Aphanomyces invadans zoospores - Afzali, Seyedeh Fatemeh; Mohd Daud, Hassan; Abdul Mutalib, Abdul Rahim (Universiti Putra Malaysia Press, 2014)
Epizootic ulcerative syndrome (EUS) is one of the seasonal and economically devastating diseases in the wild and farmed fresh water and estuarine fish. Thus, an experimental study was conducted by the Faculty of Veterinary Medicine, Universiti Putra Malaysia (UPM) from February to April 2012, to examine the susceptibility of Malaysia’s indigenous fish to EUS infection. In this experiment, forty apparently healthy moonlight gourami (Trichogaster microlepis) (10 ± 2 g body weight and 7.5 ± 1 cm in body length) were kept at 20 °C and challenged by intramuscular injection of zoospores (0.1 ml of 10,000 spores ml–1 suspension ) of Aphanomyces invadans (isolate NJM9701). Fish were observed daily for characteristic EUS clinical signs during the 14-day trial and sampled at 1, 2, 4, 6, 7, 8, 9, 10, 11, 13, 12, 14 days post-injection. The infected skin and muscle were then sampled for histopathological examination. The results demonstrated that injected fish started to develop lesions that were histopathologically and grossly identical to those found in naturally EUS-infected fish and they died within two weeks after the infection. The profoundly penetrating ulcers had characteristics such as severe dermatitis, myofibrillar degeneration, and deep necrotizing granulomatous myositis. Therefore, the result of this study proved that moonlight gourami was vulnerable to the EUS agent.